MicroRNA-27a (miR-27a) in Solid Tumors: A Review Based on Mechanisms and Clinical Observations - Zhang, Jingcheng; Cao, Zhe; Yang, Gang; You, Lei; Zhang, Taiping; Zhao, Yupei (Frontiers in Oncology, 2019)
MicroRNAs (miRNAs) are a family of highly conserved noncoding single˗stranded RNA molecules of 18 to 22 nucleotides. miRNAs silence their cognate target genes at the posttranscriptional level which have been revealed paying important roles in oncogenesis, invasion, and metastasis. MicroRNA-27a (miR-27a), transcripted by miR-27a gene, has proved to implicate with many kinds of solid tumors, showing potential as a useful biomarker or drug target for clinical application. However, even though miR-27a has been reported in many cancers, the mechanism and signal pathways of miR-27 in oncogenesis, invasion, and metastasis are still obscure. Moreover, recent studies show that miR-27a pays an important role in epithelial-mesenchymal-transition, regulating tumor immune response, and chemoresistance. In this review, we summarize the current literature demonstrating established links between miR-27a and oncogenesis with a focus on recently identified mechanisms. This review also aims to demonstrate the potential of miR-27a as a diagnostic and/or prognostic biomarker in solid tumors and to discuss the possibilities that targeting therapeutics and drug designing.